BIO?BASED MOLECULAR SWITCHES FROM ISOLONCHOCARPIN - Bongso, Anthony
A molecular switch is a synthetic molecule that can be toggled or reversibly shifted between two or more states in response to certain stimuli. The development of molecular switches, along with other artificial molecular machine (AMMs) has been projected to be a pioneer in the nano?machinery field. In general, the synthesis of molecular switches requires a long multi?step reaction followed by multiple steps of work?up and purification. Any mistakes during the process can lead to wasted resources and time. Fortunately, Indonesia is renowned for its second?highest biodiversity in the world, with a rich source of natural products. In this research, the novel first??and second-generation bio?based molecular switches based on Indonesian’s natural product, namely isolonchocarpin has been synthesized through McMurry reaction and Barton?Kellog reaction. Isolonchocarpin was chosen due to its relatively planar structure and the presence of a stereogenic center that can induce the unidirectional motion of AMMs. Isolonchocarpin have been isolated and identified from the pod peels of Tephrosia vogelii. The first?generation molecular switch S1 has been successfully synthesized with a yield of 67% (E: Z = 2:1). The second?generation molecular switch S2 has also been successfully synthesized with a yield of 41% (E: Z = 2:1). The results of the photoirradiation study shows that compound S1 performed switch from (E)?S1 to (Z)?S1 followed by photocylization. Meanwhile, S2 performed a relatively decent rates of photoisomerization (E: Z = 2:1 to 1:1). These results open the opportunity for Indonesian natural product to be utilized as building blocks in broader potential applications.